The State Of Education In Elazig During The First World War - Tatar, Özcan; Baytimur, Suha Oğuz (Fırat University, 2019)
One of the most difficult times of the Ottoman Empire, the First World War process, is known as a period of stenosis and difficulty. During this war period, there were great losses both in population and economic terms due to the battles on many fronts. In spite of the diffuculties experienced during the war period, it was tried to be active in the field of education. However, the recruitment of a large number of existing teachers has hampered education activities to a great extend.In this study which about the situation of education in Elazığ in the light of the information reflected in the inspection reports of the period. In the framework of these reports, assessments were made about the situation of the schools in Elazığ and the relations of the schools in Elazığ and the relations of teachers and students with the school.

Osmanlı Devleti’nin en zor zamanlarından biri olan I. Dünya Savaşı süreci, darlık ve zorluk dönemi olarak bilinir. Bu dönemde birçok cephede yapılan muharebeler nedeniyle, gerek nüfus, gerekse ekonomik açıdan büyük kayıplar yaşanmıştır.Devlet, söz konusu dönemde yaşadığı güçlüklere rağmen, eğitim alanında faaliyet göstermeye çalışmıştır. Ancak mevcut öğretmenlerin çoğunun silahaltına alınmış olması, eğitim faaliyetini büyük ölçüde aksatmıştır.Hazırlanan bu çalışmada, dönemin teftiş raporlarına yansımış olan bilgiler ışığında, Elazığ’daki eğitimin durumu hakkında malumat verilmiştir. Bu raporlar çerçevesinde, Elazığ’da o dönemde mevcut olan okulların durumu, öğretmen ve öğrencilerin okul ile olan irtibatları ile ilgili değerlendirmeler yapılmıştır.
I. DÜNYA SAVAŞI SIRASINDA ELAZIĞ’DA EĞİTİMİN DURUMU